Blue-emitting cationic iridium(iii) complexes featuring pyridylpyrimidine ligands and their use in sky-blue electroluminescent devices12. Issue 37 (11th September 2017) - Henwood, Adam F.; Pal, Amlan K.; Cordes, David B.; Slawin, Alexandra M. Z.; Rees, Thomas W.; Momblona, Cristina; Babaei, Azin; Pertegás, Antonio; Ortí, Enrique; Bolink, Henk J.; Baranoff, Etienne; Zysman-Colman, Eli
Abstract : The synthesis, structural and photophysical characterisation, and LEEC devices of four novel, cationic iridium(iii ) complexes are reported. Abstract : The synthesis and structural and photophysical characterisation of four novel, cationic iridium(iii ) complexes are reported. These complexes were designed to emit in the blue region of the visible spectrum without employing sp 2 carbon–fluorine bonds, which have been shown to be electrochemically unstable. Two different C ∧ N (where C ∧ N is a bidentate cyclometalating ligand possessing a nitrogen–carbon chelate) ligands [5-(4-methylpyridin-2-yl)-2, 4-dimethoxypyrimidine (Mepypyrm) and 5-(5-(trifluoromethyl)pyridine-2-yl)-2, 4-dimethoxypyrimidine (CF3 pypyrm)] combine electron-withdrawing pyrimidyl nitrogen atoms (in a para relationship with respect to the metal) with methoxy groups in a meta relationship with respect to the metal, which both inductively withdraw electron density from the metal centre, stabilizing the highest occupied molecular orbital. The result is highly efficient ( Φ PL = 73–81%) green to blue ( λ PL = 446–515 nm) emission for complexes1–4 in MeCN solution. Complex1 exhibits a broad, unstructured charge transfer (CT) emission profile, while complexes2–4 exhibit structured, vibronic emission profiles. Density Functional Theory (DFT) calculations corroborate these findings with spin density calculations predicting a T1 state that is metal-to-ligand and ligand-to-ligand (C ∧ N to N ∧ N) charge transfer ( 3 MLCT/ 3 LLCT) in nature for complex1, while complexes2–4 are predicted to exhibit ligand-centred ( 3 LC) states with spin density localised exclusively on the C ∧ N ligands. These complexes were used as emitters in sky-blue and blue-green light-emitting electrochemical cells (LEECs). The bluest of these devices (CIE: 0.23, 0.39) is among the bluest reported for any iridium-based LEEC. It is noteworthy that although the electroluminescence intensity decreases rapidly with time ( t 1/2 = 0.1–20 min), as is typical of blue-green LEECs, for devicesL1, L3 andL4 we have observed for the first time that this decay occurs without an accompanying red-shift in the CIE coordinates over time, implying that the emitter does not undergo any chemical degradation process in the non-doped zones of the device.